Emerging trends in eco-compliant, synergistic, and hybrid assembling of multifunctional polymeric bionanocomposites - Idumah, Christopher Igwe (Walter de Gruyter GmbH, 2016)
The quest to develop eco-benign polymeric hybrid materials arose out of the need to protect the environment from the harmful effects of synthetic petroleum polymeric waste and meet the specific needs of industries such as oil and gas, aerospace, automotives, packaging, electronics biomedicals, pharmaceuticals, agricultural, and construction. This has resulted in synergistic hybrid assembling of natural fibers, polymers, biopolymers, and nanoparticles. Bionanocomposites based on inorganic nanoparticle reinforced biofiber, polymers and biopolymers, and polysaccharides such as chitosan, alginate, and cellulose derivatives, and so on, exhibiting at least a dimension at the nanometer scale, are an emerging group of nanostructured hybrid materials. These hybrid bionanocomposites exhibit structural and multifunctional properties suitable for versatile applications similar to polymer nanocomposites. Their biocompatibility and biodegradability provide opportunities for applications as eco-benign green nanocomposites. This review presents state-of-the-art progress in synergistic nanotechnological assembling of bionanocomposites relative to processing technologies, product development, and applications.